Macronutrient intake and energy availability in young male elite cyclists: the importance of adequate CHO intake: CHO intake in young elite cyclists - Jakus, Tadeja; Jenko Pražnikar, Zala; Jurdana, Mihaela (Progress in Nutrition, 2022)
Aims: Macronutrient intake before, during and after exercise may influence performance and inflammatory responses in elite athletes. In this context, we analyze the adequacy of nutritional status, daily energy and macronutrient intake as well as intake during and after acute training, energy availability (EA) and inflammatory response after acute training associated with carbohydrate intake (CHO) in ten young male elite cyclists. Methods: Ten Slovenian competitive cyclist, aged between 15 and 30 years participated in this study. Energy intake (EI) and macronutrient intake were assessed using 3-day dietary protocols. Venous blood samples were collected before and after acute exercise to analyse serum biochemical parameters, as well as pro-inflammatory (CRP, IL-6 and TNF-α) and anti-inflammatory (adiponectin) cytokines. Results: The average macronutrient composition of daily EI was 6.1 g/kg body mass (BM) of CHO, 1.7 g/kg BM of protein, and 29% EI fat, and in most cases did not meet exercise intensity recommendations. Less than 50% of all participants consumed sufficient CHO daily and during exercise (mean intake was 6.1 g/kg BM and 32g/h, respectively). Protein intake was the only category in which most participants (70%) met the recommended daily amounts (1.7 g/kg BM) and the amounts during and after exercise (0.08 g/kg BM and 0.5 g/kg BM). Fat intake during (15% EI meal) and immediately after exercise (32% EI meal) exceeded the recommended amount and less than 40% of all participants adhered. EI was below estimated requirements (45 kcal/kg BM) and most of our participants had subclinical EA (35 kcal/kg FFM). We observed a positive correlation between daily CHO and EA (p=0.024) and serum ferritin (p=0.014). Finally, adequate CHO intake during and after exercise reduces pro-inflammatory IL -6. Conclusion: Young male elite cyclists did not meet energy demands and specific macronutrient requirements. Inadequate carbohydrate intake, low EA, and ferritin concentrations may exacerbate inflammation after acute exercise. These findings may have both short- and long-term implications for the health and performance of young cyclists.